2008
DOI: 10.1080/00016480801891710
|View full text |Cite
|
Sign up to set email alerts
|

Non-sentinel node tumor invasion in oropharyngeal and oral cancer: risk of misdiagnosis of metastasis

Abstract: We detected a total of 32 SLNs in 21 of 22 patients. Ipsilateral neck node location was observed in 18 patients and bilateral in 3. We observed 10 patients with true positive SLNs (3 patients had micrometastases), indicating occult metastases. We harvested a total of 454 nodes in our selective neck dissections, 19 of which presented metastatic invasion. We identified four patients with positive non-sentinel nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…In a recent work by Atula et al,12 35 patients with oral or oropharyngal SCC who had positive SN showed an overall incidence of tumor deposits in the NSN of 37% (13/35) examined at 2 mm intervals with H&E and IHC. In a prospective study of 22 patients with oral or oropharyngeal SCC T1–T3N0 who had SNB and subsequent neck dissection, Santaolalla et al13 examined the NSN by routine hilar bisectioning and H&E staining and found metastatic deposits in 4 patients (18%) who had negative or missing SN. The authors argued that these false negative results could be due to the location of tumor close to the midline and/or bilateral lymphatic drainage patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work by Atula et al,12 35 patients with oral or oropharyngal SCC who had positive SN showed an overall incidence of tumor deposits in the NSN of 37% (13/35) examined at 2 mm intervals with H&E and IHC. In a prospective study of 22 patients with oral or oropharyngeal SCC T1–T3N0 who had SNB and subsequent neck dissection, Santaolalla et al13 examined the NSN by routine hilar bisectioning and H&E staining and found metastatic deposits in 4 patients (18%) who had negative or missing SN. The authors argued that these false negative results could be due to the location of tumor close to the midline and/or bilateral lymphatic drainage patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Two authors individually collected data from included articles in forms commensurate with each other. Diagnostic accuracy, represented by DOR, summary receiver operating characteristic (SROC) curve, and area under the curve (AUC), was calculated 1,5,11–102 . DOR was calculated as (true positive [TP]/false positive [FP])/(false negative [FN]/true negative [TN]) to assess diagnostic accuracy with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…SLNB uses frozen section analysis with H&E during surgery to determine the presence of metastasis in cancer. The conventional method is usually paraffin blocks followed by H&E staining to examine for possible metastasis and further immunohistochemical (IHC) [83,85,87,88,91,92,96,98,101] analysis for cytokeratin (AE1/AE3) [38,61,63,64,69,72,74,75,77,81,86] to reveal any undetected micro-metastasis if the node was free from tumors. However, the intraoperative pathology of SLNB is only moderately sensitive, and the final pathology examination might require several days.…”
Section: Tissue Biopsymentioning
confidence: 99%